ANALYSIS OF THE IMPACT OF ANTI-BULLYING SOCIALIZATION ON THE SOCIAL AWARENESS OF ELEMENTARY SCHOOL STUDENTS IN SIANGGUNAN VILLAGE, BATANGTORU DISTRICT, SOUTH TAPANULI REGENCY - Khoiruddin Nasution; Safran Efendi Pasaribu; Suryanto Suryanto; Mukti Simamora (Program Pascasarjana UIN Sumatera Utara, 2026)
This study aims to analyze the impact of anti-bullying socialization on the social awareness of elementary school students in Sianggunan Village, Batangtoru District, South Tapanuli Regency. This study used a quantitative approach with a pre-experimental one-group pretest-posttest design. The research sample consisted of 30 students selected using a purposive sampling technique. The instrument used was a questionnaire to measure students' social awareness. The results showed that the average pretest score of 64.30 increased to 81.75 in the posttest. The results of the paired sample t-test showed a significance value of 0.000 (p < 0.05), which means there is a significant effect of anti-bullying socialization on students' social awareness. Thus, anti-bullying socialization is proven effective in increasing students' social awareness, especially in the aspects of empathy, social concern, and attitudes towards bullying behavior.